Rethinking the City Symphony after the Age of Industry : Harun Farocki and the ‘City Film’ - Cowan, Michael (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2008)
Abstract Harun Farocki’s films and installation works have often revisited the question—central to the history of experimental filmmaking—of the city and its representability. Focusing on Farocki’s recent installation Gegen-Musik, this article explores his efforts to reconfigure the genre of the Stadtsinfonie (city symphony) for a post-industrial era. To the difference of other recent efforts to renew modernist strategies for representing the city, Farocki interrogates the possibility of such a genre in an era characterized by the marginalization of human labor, industry and the image itself.